Integrated mechanics for design of the hybrid electrical aircushion track vehicle for swamp peat - Rahman, Mohammed Ataur; Hossain, Altab; Mohiuddin, A. K. M. (2008)
This paper presents an integrated mechanics for the design of hybrid electrical aircushion tracked vehicle (HETAV). Mechanics are incorporated with accounting the kinematics and dynamics behaviors of the vehicle tracked and air-cushion system. The air-cushion of HETAV is protected with a novel-design auto-adjusting supporting (AAS) system which can adjust automatically with absorbing the horizontal and vertical displacement of the air-cushion system. Simulated tractive effort has shown the requirement to develop an additional thrust to overcome the total motion resistance of the vehicle. A propeller is equipped with the vehicle to develop additional thrust for overcoming the dragging motion resistance. The performance of the HETAV is defined by traction and motion resistance. The simulation results show that the vehicle load distribution to the air-cushion system would not be too high since the power consumption by the air-cushion drag motion resistance is affected significantly on the total power requirement as well as the propeller develops an additional thrust of 0.2 kN while the track system develops only 1.674 kN for the vehicle loading condition of 2.04 kN.